Gender and age differences in forgivingness in Italian and Polish samples. Issue 6 (June 2022) - Cabras, Cristina; Kaleta, Kinga; Mróz, Justyna; Loi, Giorgia; Sechi, Cristina
Abstract: This study explores gender and age differences in forgivingness using the crosscultural and stress-and-coping perspective. Polish and Italian versions of the Heartland Forgiveness scale (HFS) were used. The sample consisted of 1957 individuals aged 18–80 (61% females and 39% males). A 3-way between groups ANOVA was used to examine the main effects and interactions of country, age and gender as they relate to total HFS score. Post-hoc analyses were performed where appropriate. The results revealed that Polish and Italian respondents did not differ in the level of the general tendency to forgive. Gender differences in trait forgiveness were reported in whole sample and in Italian subsample, showing males to be more forgiving than females. Further, our results for all study participants, in Polish subsample and among Italian males showed that older adults were more forgiving than young respondents, which is consistent with the previous findings showing an increase in forgivingness with age. Abstract : Forgiveness; Gender; Age; European countries.